Clinical and morphological features of the cesarean scar pregnancy - N.P. Honcharuk; O.O. Diadyk; N.R. Kovyda; O.Y. Lysenko; O.B. Shelest (Репродуктивная эндокринология, 2022)
The features of timely diagnosis and possible risks of the cesarean scar pregnancy are demonstrated on the example of a clinical case. This article presents analysis of pregnancy and childbirth of patient Sh., who was in the Obstetrics Department of the Kyiv City Maternity Hospital No. 1, as well as the results of a detailed morphological study of tissue characteristics during pregnancy in the scar on the uterus. A complete presentation of the chorion with localization in the area of the postoperative scar and a defect in the uterine wall was established at the first and second ultrasound screening. The woman was informed about pregnancy risks, but she insisted on prolonging the pregnancy. A planned surgical intervention was performed in the period of 36–37 weeks. A bottom caesarean section was performed and a girl weighing 3610 g, height 55 cm was removed. Intraoperatively confirmed deformation with a defect of the front uterus wall in the area of a postoperative scar measuring 10 × 12 cm, filled with placental tissue in the form of aneurysmal altered vessels. It was confirmed that placenta grew into the wall of the uterus over the entire area of its location, which occupied the entire lower segment on the entire circumference of the uterine body. At the same time, a significant deformation of the front and back walls of the uterus was noted. Morphological examination revealed hypoxic degenerative changes in the placenta, from the side of the parietal plate, with sclerosis, hyalinosis and deposition of fibrinoid in the villi, as well as the presence of hemorrhages, petrifications and the formation of conglomerates and bridges between them. Conclusions. It was founded the leading role in the mechanism of formation of atypical localization of pregnancy in the area of the scar after previous cesarean section was altered uterus tissue, where implantation occurred. There is a high probability of transition from ectopic pregnancy to scarring from liquid forms of ectopic pregnancy in the category of more frequent pathologies due to the increase in the frequency of cesarean sections.